2020
DOI: 10.3390/ijms21249475
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nucleoporin Elys in Nuclear Pore Complex Assembly and Regulation of Genome Architecture

Abstract: For a long time, the nuclear lamina was thought to be the sole scaffold for the attachment of chromosomes to the nuclear envelope (NE) in metazoans. However, accumulating evidence indicates that nuclear pore complexes (NPCs) comprised of nucleoporins (Nups) participate in this process as well. One of the Nups, Elys, initiates NPC reassembly at the end of mitosis. Elys directly binds the decondensing chromatin and interacts with the Nup107–160 subcomplex of NPCs, thus serving as a seeding point for the subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 100 publications
1
16
0
Order By: Relevance
“…Elys, one of the NPC proteins found in the IP-MS analyses, is a core scaffold protein of the NPC and has been shown to play a role in genome architecture regulation (Shevelyov, 2020). Elys binds across the genome at sites that intersect with multiple other NPC proteins (Gozalo et al, 2020; Pascual-Garcia et al, 2017; Shevelyov, 2020) and has also been shown to bind and relocate specific loci to the NPC (Scholz et al, 2019). Taking advantage of published Elys chromatin immunoprecipitation with sequencing (ChIP-seq) datasets from third instar Drosophila larvae brains, we found that Elys binds specifically at the hb gene intron (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elys, one of the NPC proteins found in the IP-MS analyses, is a core scaffold protein of the NPC and has been shown to play a role in genome architecture regulation (Shevelyov, 2020). Elys binds across the genome at sites that intersect with multiple other NPC proteins (Gozalo et al, 2020; Pascual-Garcia et al, 2017; Shevelyov, 2020) and has also been shown to bind and relocate specific loci to the NPC (Scholz et al, 2019). Taking advantage of published Elys chromatin immunoprecipitation with sequencing (ChIP-seq) datasets from third instar Drosophila larvae brains, we found that Elys binds specifically at the hb gene intron (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Elys, one of the NPC proteins found in the IP-MS analyses, is a core scaffold protein of the NPC and has been shown to play a role in genome architecture regulation (Shevelyov, 2020).…”
Section: Dan Interacts With Nucleopore Complex Proteins Which Are Req...mentioning
confidence: 99%
See 1 more Smart Citation
“…3A). We used Elys protein levels as a proxy for the Nup98-96 depletion since these proteins are in the same complex (Franz et al, 2007;Gillespie et al, 2007;Rasala et al, 2006;Shevelyov, 2020) and we consistently observed a reduction in Elys protein in the Nup98-96 depletion (Supp. Fig.…”
Section: Orc Binding To Chromatin Partially Depends On Elysmentioning
confidence: 99%
“…In addition to their canonical function at NPCs, a subset of Nups bind to chromatin and regulate genome structure and function. For example, the nucleoporin Elys binds to chromatin in late mitosis and is required to assemble nuclear pore complexes onto chromatin prior to their insertion into the nuclear membrane (Franz et al, 2007; Galy et al, 2006; Gillespie et al, 2007; Rasala et al, 2006; Shevelyov, 2020). More recent work; however, has demonstrated that several Nups regulate both transcription and chromatin condensation (Capelson et al, 2010; Kalverda et al, 2010; Kuhn et al, 2019; Panda et al, 2014; Pascual-Garcia et al, 2014, 2017; Raices and D’Angelo, 2017; Vaquerizas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%